Development of a Desktop Application Based on Interactive Learning Multimedia for Introduction to Computer Hardware for Students of the Madrasah Ibtidaiyah Teacher Education Study Program - Santoso, Agung Budi; Utomo, Nur Fadli (Journal of Elementary Educational Research, 2024)
This research is intended to create and develop interactive multimedia-based desktop application products that are effective and have advantages for use in learning to introduce computer hardware in PGMI study programs, and evaluate the benefits of these products in improving PGMI student learning outcomes. The development process of this research adopted the Alessi & Trollip development model with the following procedures, namely stage planning, stage design, and stage development. Product trials include an alpha test carried out by media experts and material experts, as well as a beta test involving 21 PGMI study program students. Data collection was carried out through interviews, observations and questionnaires which were given to media experts, material experts and students as users. The results of the research show that interactive multimedia learning has been packaged in Disc format, and this multimedia product is considered very feasible by material experts, media experts, and trial participants.